Administrative and environmental determinants of Agricultural Policy of the European Union - Maciej Jabłoński (Studia Ecologiae et Bioethicae)
Development of Agricultural Policy of the European Union is a good example of historical and ideological changes that took place recently in Europe. At first largely socialist it has changed over the decades into a policy that promotes active participation. The increased spending on rural development has increased both awareness and, as a result, compliance with environmental standards.